“Propuesta de un modelo didáctico para el proceso de enseñanza aprendizaje en la universidad nacional de san martín tarapoto-2014” - Ríos Pérez, Juan Segundo (2015)
The instructional model far teaching-learning process competency at the National University of San Martin-Tarapoto DMTLP-UNSM-T., Derives from the observation of the reality of an increasingly competitive world that demands of teaching practice, ensures integral training of students in higher education, guided the skills to enable them to contribute effectively in building a new society. The aim of the proposal is to improve the standard of teaching and learning through its application competence approach, and it contributes to the process of accreditation of the UNSM-T, framed in its vision to 2021. The development of research has been aimed at discovering the pedagogical training of the teaching-learning process-TLP forms applied in the National University of San Martin to 2014; observing their interna! and externa! connections, contributors of knowledge in the current training of students. Understanding, describing, explaining and interpreting with rational rigor with the qualitative approach the characteristics of the problem situation in investigation. In this context the critica! sociopolitical paradigm which emerge of the lntegrators alternative or didactic models, which are the basis of the proposal: Didactic model with competences approach of the DMTLP UNSM-T, which includes the contributions of the models: Tetrahedral, Cyclic and Dynamic Collaborative and through its application, to transcend the limitations that shows the didactic act of professor in the National University of San Martin - Tarapoto to 2014 and the achievement of its vision to 2021.